The climate science for service partnership Brazil. Issue 1 (22nd January 2022) - Jones, Chris D.
Abstract: Human activities continue to warm our climate in ways unprecedented in thousands of years. The latest Intergovernmental Panel on Climate Change (IPCC) report confirms our role in this, and that more frequent and extreme events and impacts are being felt right now in all areas of the world. It is clear that we must adapt to some level of changes already occurring whilst also reducing our emissions to limit further damage and unmanageable impacts. What this means for society requires understanding at local levels to aide decision‐making. The Climate Science for Service Partnership Brazil (CSSP Brazil) supports collaborative research between Brazil and U.K. partners to improve climate resilience and sustainability with particular focus on Brazil but with underpinning capability applicable more widely. Abstract : Our climate is changing—we must adapt to some changes already with us, and reduce emissions to limit the extent of future impacts. The Climate Science for Service Partnership Brazil (CSSP Brazil) is a project which supports collaborative research between Brazil and U.K. partners to improve climate resilience and sustainability in Brazil. The project brings together experts in carbon cycle science and ecosystem resilience; climate modellers looking at extreme rainfall across timescales; and climate impacts experts. This overview paper describes the many wide‐ranging outcomes from the project.